The use of cluster analysis at the development of approaches on selection and administration of treatment to HIV-infected patients - Nadezhda A. Gudilina; El’vira S. Ivanova; Andrey V. Sibiryakov; Natal’ya V. Mekhonoshina; Natal’ya B. Rostova; Rustam A. Fayzrakhmanov (Бюллетень сибирской медицины)
The purpose of the study is the formation production rules for selecting combinations of antiretroviral drugs for patients with HIV infection for optimal therapy.Materials and methods. The cluster analysis base is the choice of patients whose treatment can be assessed as successful. As a result of the selection of effective treatment cases, 79 patients were left in the study out of 123 examined cards of patients treated at the Perm Regional AIDS and Infectious Diseases Center. As input parameters for the cluster analysis, the patient’s sex, the stage of the main disease at the time of antiretroviral therapy, the way of HIV infection, and presence of opportunistic diseases were selected. As an output variable, the prescribed treatment regimen was adopted. Analysis of treatment of patients (79 cases) showed that the optimal solution is using nine clusters.Results. The results of this analysis allow us to formulate production rules for the selection of antiretroviral drugs to create an expert system that allows us to optimize the rational choice, designation and use of drugs for the treatment of HIV-infected patients.